Epidemiological and Clinical Features of COVID-19 Patients at National Emergency Hospital Wisma Atlet Kemayoran, Jakarta, Indonesia - Susanto, Agus Dwi; Rozaliyani, Anna; Prasetyo, Budi; Agustin, Heidy; Baskoro, Hario; Arifin, Arief Riadi; Pratama, Satria; Zaini, Jamal; Hasto, Bambang Dwi; Ratmono, Tugas; Savitri, Ary Indriana; Samoedro, Erlang; Husain, Bahtiar; Nawas, Arifin; Burhan, Erlina (UI Scholars Hub, 2021)
The emergency hospital is intended to prevent transmission of COVID-19 in the community by isolating patients without symptoms, with mild or moderate symptoms. This study evaluated the clinical characteristics and outcomes of COVID-19 patients who were admitted to this facility. This retrospective study re-viewed data of patients treated at the National Emergency Hospital Wisma Atlet Kemayoran in Jakarta, Indonesia, from March 23 to April 30, 2020. Patient characteristics (clinical symptoms, laboratory test results, Chest X-Ray, SARS-CoV-2 immunoserology, and RT-PCR results from nasopharyngeal/ oropharyngeal preparations) were compared between severity groups. There were 413 COVID-19 cases analyzed, of which 190 (46%) were asymptomatic, 93 (22.5%) were mild, and 130 (31.5%) were moderate cases. Most asymptomatic cases were male, with young age, and without comorbidity. Mild cases were dominated by female and young patients, while most moderate cases were male and older patients. The number of patients with comorbidities was higher in mild and mod-erate cases. The patient’s overall outcome was good and did not differ based on the severity of symptoms. Despite the many challenges, patients with moderate symptoms can be safely treated in the emergency hospital.